Pengaruh Ukuran Perusahaan, Roe, Dan Current Ratio Terhadap Struktur Modal Dimoderating Sales Growth Pada Perusahaan Perdagangan, Jasa, Dan Investasi Di BEI - Ade Hartati Girsang; Clara Putri Simamora; Tetty Tiurma Uli Sipahutar (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to understand the effect of Firm Size, ROE, Current Ratio on Capital Structure moderated by Sales Growth. The population used in this research is trading, service and investment companies listed on the IDX in 2016-2019. According to the total sample criteria, 28 companies were selected from 164 companies. To get real results, we try to test each variable according to the hypothesis. This research uses multiple linear regression analysis methods as well as Moderated Regression Analysis (MRA) which is preceded by descriptive analysis and continued with classical assumption tests. The hypothesis experiment used the F test analysis tool and the t test. The conclusion of this research is that firm size and ROE do not have a partial effect on capital structure, while the current ratio has a partial and significant negative effect on capital structure. The results of the moderation regression analysis are that Sales Growth is unable to moderate Firm Size, ROE , and Current Ratio to Capital Structure. Keywords: Firm Size, ROE, Current Ratio, Sales Growth, Capital Structure.